Peningkatan Kewaspadaan Masyarakat Dengan Mitigasi Perubahan Iklim Di Desa Mundu - Muhammad Tegar; Muslim Afandi (Universitas Muhammadiyah Surakarta, 2026)
This study aims to enhance community awareness and resilience in Mundu Village against climate change through community-based adaptation and mitigation strategies. Utilizing a Participatory Action Research (PAR) approach, the program engages local residents in problem identification, solution implementation, and impact evaluation. Findings indicate that Mundu Village faces high vulnerability due to its geographic location, hydrological conditions, and the dominance of vulnerable groups within its social structure. Nevertheless, the community demonstrates strong adaptive capacity supported by local institutions, sustainable agricultural practices, and access to renewable energy such as biogas. Adaptation strategies focus on managing wind hazards, flooding, and climate-related diseases, while mitigation efforts include energy conservation, waste management, clean water provision, and tree planting. Active community involvement and the integration of programs into village development plans are key success factors. Education, cross-sector collaboration, and institutional strengthening play crucial roles in building sustainable climate resilience.